Fate of household and personal care chemicals in typical urban wastewater treatment plants indicate different seasonal patterns and removal mechanisms. (1st February 2022) - Li, Wen-Long; Zhang, Zi-Feng; Kilgallon, John; Sparham, Chris; Li, Yi-Fan; Yuan, Yi-Xing
Abstract: Studies on the presence and fate of household and personal care chemicals (HPCCs) in wastewater treatment plants (WWTPs) are important due to their increasing consumption worldwide. The seasonal patterns and removal mechanisms of HPCCs are not well understood for WWTPs that apply different treatment technologies. To answer these questions, the sewage and sludge samples were taken from 10 typical WWTPs in Northeast China. Levels of UV filters in the influents in the warm season were significantly greater than that of the cold season ( p < 0.05). Significant seasonal differences were found for the removals of many HPCCs. Results revealed that the highest removal efficiencies were found for linear alkylbenzene sulphonates with values ranging from 97.2% to 99.7%, and the values were 50.0%–99.9% for other HPCCs. The SimpleTreat model demonstrated that the studied WWTPs were operating with high efficiency at the time of sampling. The sorption of HPCCs to sludge can be strongly associated with their physicochemical parameters. Mass balance calculation suggested that sorption was the dominant mechanism for the removal of antimicrobials, while degradation and/or biotransformation were the other mechanisms for removing the most HPCCs in the WWTPs. This study real the factors influencing the seasonal patterns and removal mechanisms which imply the need for further studies to fully understands the plant and human health implications as sludge could be used in the municipal land application of biosolids. Graphical abstract: Image 1 Highlights: Seasonal patterns influenced the levels and removals of targeted compounds. The studied wastewater treatment plants were operating at high efficiencies. Solid-liquid distribution was associated with physicochemical properties. Antimicrobials were removed mainly through sorption to the sludge.